Toward a New Scribal Tendency: Reciprocal Corruptions and the Text of 1 Corinthians 8:2-3 - Letteney, Mark ca. 21. Jh. (Journal of Biblical literature, 2016)
This article demonstrates that there are strong intrinsic and transcriptional grounds to posit the priority of the "shorter text" of 1 Cor 8:2-3 and explores the grounds for the longer text's appearance in the context of a developing early Christian interest in divine reciprocity in love and knowledge.